2023
DOI: 10.1007/s00405-022-07814-9
|View full text |Cite
|
Sign up to set email alerts
|

A Google Trends analysis revealed global public interest and awareness of nasal polyps

Abstract: Introduction Nasal polyps (NPs) is a common upper airway inflammatory disorder with a huge negative burden on both the quality of life and costs to patients. However, NPs patients remain undiagnosed and untreated in a timely, which may be due to a lack of disease-related awareness. Google Trends (GT) is an online and open tool, which can provide real-world data on health informatics worldwide. Objectives This study aimed to explore global public interest and awareness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the medical field, some examples are forecasting epidemiological traits of allergic rhinitis, establishing correlation between asthma hospitalizations and common cold, revealing spikes of interest in nasal polyps, among many others. 5 , 6 , 7 The spike of interest in milk allergy in 2021 for 6 out of the 10 selected countries might be related to the findings of a study in the UK 8 which showed that cow's milk allergy may be the root of three‐quarters of newborns' two or more allergic symptoms at some point in the first year of life. Another possible reason for the trending phenomenon may be the hospitalizations and deaths of infants in the USA because of contaminated Abott baby formula products in May of 2022.…”
Section: Most Searched Topicsmentioning
confidence: 99%
“…In the medical field, some examples are forecasting epidemiological traits of allergic rhinitis, establishing correlation between asthma hospitalizations and common cold, revealing spikes of interest in nasal polyps, among many others. 5 , 6 , 7 The spike of interest in milk allergy in 2021 for 6 out of the 10 selected countries might be related to the findings of a study in the UK 8 which showed that cow's milk allergy may be the root of three‐quarters of newborns' two or more allergic symptoms at some point in the first year of life. Another possible reason for the trending phenomenon may be the hospitalizations and deaths of infants in the USA because of contaminated Abott baby formula products in May of 2022.…”
Section: Most Searched Topicsmentioning
confidence: 99%